Mixed micellization study of dodecyltrimethylammonium chloride and cetyltrimethylammonium bromide mixture in aqueous/urea medium at different temperatures: Theoretical and experimental view. (19th July 2018) - Mahbub, Shamim; Rub, Malik Abdul; Hoque, Md. Anamul; Khan, Mohammed Abdullah
Abstract: The behavior of mixed micelle formation between two cationic surfactants‐dodecyltrimethylammonium chloride (DTAC) and cetyltrimethylammonium bromide (CTAB) in absence/attendance of urea has been investigated by means of conductivity measurements over temperature range of 298.15 to 318.15 K. Lower magnitudes of the critical micelle concentration from their ideal values imply the strong interaction between the studied amphiphiles. The micellar mole fraction ( X 1 ) on the basis of the different proposed model (Rubingh, Motomura & Rodenas) and the ideal micellar mole fraction ( X id ) were evaluated, and estimated results imply the high contribution of CTAB in the mixed micelle formation that enhances with the augment of the mole fraction of the CTAB. The values of activity coefficients ( f 1 and f 2 ) (less than unity) and negative values of the interaction parameter ( β ) in all cases signify the attractive interaction between the amphiphiles studied. Spontaneous mixed micelle formation between the studied amphiphiles (dodecyltrimethylammonium chloride and CTAB) was indicated by the negative magnitudes of free energy of micellization ( ΔG m 0 ). The negative values of excess free energy of micellization ( ΔG ex ) indicate the higher stability of the mixed micelle compared with the single micelle. The standard enthalpy change of micellization ( ΔH m 0 ) and standard entropy change of micellization ( ΔS m 0 ) were also calculated and discussed. Abstract : Mixed micelle formation between two cationic surfactants in absence/attendance of urea has been investigated using conductivity measurements over temperature range of 298.15 to 318.15 K. The micellar mole fraction ( X 1) on the basis of the different proposed model (Rubingh, Motomura and Rodenas) were evaluated. The negative values of the interaction parameter ( β ) in all cases signify the attractive interaction between the components. The standard enthalpy change of micellization ( ΔH m 0 ) and standard entropy change of micellization ( ΔS m 0 ) were also calculated and discussed. Representative plot of cmc of DTAC vs. mole fraction of CTAB at 298.15 K in aqueous solution.